The use of online dictionaries in video-mediated L2 interactions for the social accomplishment of Virtual Exchange tasks. (June 2022) - Çolak, Fulya; Balaman, Ufuk
Abstract: Mobile applications and dedicated websites as online dictionaries have been common resources in language learning and teaching settings for years. Primarily used for looking up unknown words in reading, writing, and vocabulary learning activities, online dictionaries have been considered highly feasible, individual learning materials. However, their situated use in synchronous video-mediated interactions has remained largely unexplored despite their potential to help L2 learners resolve word-knowledge-related troubles, thus creating opportunities for meaning negotiation. Using Multimodal Conversation Analysis, this study describes the active use of online dictionaries in task-oriented video-mediated L2 interactions of Virtual Exchange participants in higher education. The close examination of the screen-recorded interactions shows that online dictionaries play an essential role in the social accomplishment of intercultural tasks. The findings indicate that L2 learners do not only look up unknown words, but they also look up the synonyms of already known words and validate their existing knowledge. Moreover, online dictionaries operate in a context-specific sequential environment consisting of diverse participant roles (describer/recipient), embodied actions, and grammatical action formats. Additionally, we observe that Wikipedia and image search emerge as supplementary tools to dictionary look-ups. The findings bring new insights into computer assisted language learning, video-mediated interactions, and Virtual Exchange.